MINIMUM PROGRAM GRAPH COVERAGE ALGORITHM - M. M. Aripov (Galaxy International Interdisciplinary Research Journal, 2022)
Structural methods for program testing are described, such as branch testing, program verification, symbolic testing, and generating structural tests. An algorithm for the minimum coverage of the program graph based on the packing adjacency matrix and a specific example of the minimum coverage of the program graph are given.